PENCEGAHAN DISFAGIA PADA LANSIA MELALUI EDUKASI MODIFIKASI MAKANAN - Anitasari Roza Shalsabila; Cep Willy Setiawan; Faisal Kusumah; Neny Widyana (Pusat Penelitian dan Pengabdian pada Masyarakat (P3M), 2025)
Abstract Dysphagia is a swallowing disorder commonly experienced by older adults and is often overlooked because it is considered a normal part of the aging process. If left unmanaged, dysphagia may lead to serious complications such as choking, aspiration, malnutrition, and decreased quality of life. This study aimed to analyze dysphagia prevention in older adults through food modification education. A quantitative study using a one-group pretest–posttest quasi-experimental design was conducted. The participants consisted of 29 older adults selected through purposive sampling. A pretest was administered to assess baseline knowledge regarding dysphagia prevention, followed by an educational intervention that included dysphagia education, food texture modification, safe eating positions, and swallowing exercises. A total of seven participants completed both the pretest and posttest assessments. The results showed an improvement in posttest scores compared to pretest scores among participants who completed the intervention, particularly in understanding appropriate food textures and safe eating positions. These findings indicate that food modification education is an effective preventive and educational approach for dysphagia prevention in older adults. Continuous and structured implementation of this education is recommended to support safe eating practices and improve the quality of life of older adults. Keywords: dysphagia, older adults, food texture modification, swallowing education, safe eating